Age castration of Nellore males on the profile of fatty acids of meat - Regis Luis Missio (Semina: Ciências Agrárias, 2017)
This study aimed to evaluate the cholesterol content, ?-tocopherol and fatty acids in the meat of Nellore young bulls or steers castrated at different ages, 13 or 18 months. The animals were confined for 100 days and slaughtered at 22 months of age. The experimental design was completely randomized with three treatments, using 12 repetitions. The levels of palmitic acid (26.39%), stearic (24.39%), myristic (3.01%) and total saturated fatty acids were not altered by sexual condition or castration age. Oleic was the fatty acid with the highest average participation in the meat (34.54%), and lower content in the meat of young bulls in relation to the castrated. The content of total unsaturated fatty acids was lower in the young bulls in relation to castrated at 18 months, which did not differ from castrated at 12 months. The content of total polyunsaturated fatty acids was increased by elevation of the castration age, being similar between young bulls and castrated at 18 months. The ratio ?6/?3 was not altered by sexual condition or castration age. Castration at the beginning of the finishing period increases the content of beneficial fatty acids to health in relation to castrated in the first third of backgrounding.